2021
DOI: 10.1007/s12666-021-02271-0
|View full text |Cite
|
Sign up to set email alerts
|

Burr Reduction in Drilling Titanium using Drills with Peripheral Slits

Abstract: Drilling of titanium alloy results in considerable burrs at the exit surface of a hole. The burrs deteriorate quality of hole surfaces and can cause misalignment during assembly. Therefore, burr minimization while drilling is necessary. In this study, innovative chamfered drills with slits have been developed to reduce the burr height and thrust forces. Dry drilling experiments were conducted using chamfered drills without slits and with slits (CWS) having four different point angles. Drilling performance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…By studying the functional relationship between the fitting factor and the response value of the multiple quadratic regression equation, the prediction model within the parameter range is determined. As shown in equation (2).…”
Section: Experimental Methods and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…By studying the functional relationship between the fitting factor and the response value of the multiple quadratic regression equation, the prediction model within the parameter range is determined. As shown in equation (2).…”
Section: Experimental Methods and Experimental Designmentioning
confidence: 99%
“…Many scholars have studied the burrs produced by the twist drill drilling process. Gajrani et al 2 used seamless and combined chamfer drills to drill titanium workpieces to study burr height, thrust, and chip shape. The results showed that the burr height generated during the drilling process of the slotted chamfered bit was 48.5% lower than that of the conventional bit, and the thrust was reduced by 5.5%.…”
Section: Introductionmentioning
confidence: 99%